Inspections From 1927 and 1928 as a Supervision Measure over the Municipal Economy of Torun in the Interwar Period - Anna Tarnowska (Prawo Budżetowe Państwa i Samorządu, 2014)
The author analyzed the legal solutions for the supervision of municipal economy existing in the former Prussian District, in the western territories of the Second Republic Poland (1920–1939). Against this background, she examined archival sources, documenting audits carried out by the government administration 1927 and 1928. Both inspections resulted in critical conclusions, which finally led to the most radical supervision measure – dissolution of the city council, and prior municipal elections.